Acetylated Hyaluronic Acid: Enhanced Bioavailability and Biological Studies. (7th July 2014) - Saturnino, Carmela; Sinicropi, Maria Stefania; Parisi, Ortensia Ilaria; Iacopetta, Domenico; Popolo, Ada; Marzocco, Stefania; Autore, Giuseppina; Caruso, Anna; Cappello, Anna Rita; Longo, Pasquale; Puoci, Francesco
Abstract : Hyaluronic acid (HA), a macropolysaccharidic component of the extracellular matrix, is common to most species and it is found in many sites of the human body, including skin and soft tissue. Not only does HA play a variety of roles in physiologic and in pathologic events, but it also has been extensively employed in cosmetic and skin-care products as drug delivery agent or for several biomedical applications. The most important limitations of HA are due to its short half-life and quick degradation in vivo and its consequently poor bioavailability. In the aim to overcome these difficulties, HA is generally subjected to several chemical changes. In this paper we obtained an acetylated form of HA with increased bioavailability with respect to the HA free form. Furthermore, an improved radical scavenging and anti-inflammatory activity has been evidenced, respectively, on ABTS radical cation and murine monocyte/macrophage cell lines (J774.A1).